Model Baru Pelayanan Administrasi Pemerintahan Daerah dalam Era New Normal di Indonesia - Baskara Adyaksa Lerrick (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2022)
This study departs from a new habit adaptation movement that changes people's social interactions as a rational choice amid the threat of the Covid-19 outbreak. The purpose of this article is to empirically test that the current model of local government administration services in the island sub-district is very inefficient and less productive so that it has an impact on meeting the basic needs of the community comfortably and equitably. Furthermore, the study offers a new model for Duo-TM, namely Face and Machine Meeting. This article demonstrates the need for empirical studies in the development of local government administrative service models to trace the difficulties and geographical risks caused by the Covid-19 outbreak. This is especially relevant if the author refers to the reasons for massive changes in various social dimensions and forces the adaptation of new habits. On the other hand, the era of the industrial revolution 4.0 places the power of technology and information as a means of innovating services that are convenient, fast, cheap, and of high quality